2017
DOI: 10.14738/assrj.421.3756
|View full text |Cite
|
Sign up to set email alerts
|

Student Expectations and Quality of Postgraduate Education: The Case for Public Universities in Uganda

Abstract: In order to chant John Stuart Mill’s Utility Theory in Service Delivery, this study focuses on the quality of student support in Postgraduate Education at Makerere University’s College of Education and External Studies (CEES). Using 50 Masters’ and Doctoral Student respondents, the study investigated an alleged gap between students’ expectations and experiences of service quality in Postgraduate programs offered by the College. Four dimensions play a cardinal role in the measurement of student support service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…He recommends that implementing comprehensive capacity-building programmes like training and development alongside financial management strategies can be useful in attaining the desired objectives. Findings by Kaggwa et al . (2017) on students' expectations of a postgraduate programmes at College of Education and External Studies, Makerere University found that there was a gap between expectations of students and what was offered by the college.…”
Section: The Case Of Ugandamentioning
confidence: 84%
See 1 more Smart Citation
“…He recommends that implementing comprehensive capacity-building programmes like training and development alongside financial management strategies can be useful in attaining the desired objectives. Findings by Kaggwa et al . (2017) on students' expectations of a postgraduate programmes at College of Education and External Studies, Makerere University found that there was a gap between expectations of students and what was offered by the college.…”
Section: The Case Of Ugandamentioning
confidence: 84%
“…He recommends that implementing comprehensive capacity-building programmes like training and development alongside financial management strategies can be useful in attaining the desired objectives. Findings by Kaggwa et al (2017) on students' expectations of a postgraduate programmes at College of Education and External Studies, Makerere University found that there was a gap between expectations of students and what was offered by the college. Organisations in Uganda just like any other sub-Saharan African country, not only face shortages of resources, but also HR challenges and managerial incompetencies (Mwita et al, 2009) and will therefore require an effective HR capacity-building system embedded within the organization, linked to a HEI and strictly supervised by the human resource department and emphasising work-based postgraduate education.…”
Section: Mid-career Development Through Postgraduate Educationmentioning
confidence: 99%